(untitled) (Altre Modernità, 2025)
In his repertoires, Ermanno Cavazzoni collects idiotic characters and useless writers, in the wake of Gianni Celati’s weirdos, who are openly created in opposition to modern civilization. Through the principle of synecdoche, these few figures represent humanity in general. In Cavazzoni’s production, the rigidity of the repertorial structure, which looks to the models of medieval exempla, hagiographic stories and the most fashionable teaching manuals for young writers, comes into crisis, deviating into the parodic region of counter-possibilities. What we intend to emphasize here is how the Oulipian matrix of these narratives, declared in the combinatorial table of Gli scrittori inutili, appears partly different from that of the French authors. Cavazzoni suggests meaning beyond the self-imposed norms in a more explicit, subversive way. The author shows the rule and the tension toward an uncontrollable liquidity, pointing out the radical pessimism about humankind. In this perspective, the social function of the man of letters also fails: still on the model of Celati, and in contrast with the collaborative spirit of Oulipo, Cavazzoni reiterates his preference towards the figure of the hermit, for the secluded, resorting to the collection of lives to demonstrate his theorem.